Quantification of HDL Proteins, Cardiac Events, and Mortality in Patients with Type 2 Diabetes on Hemodialysis - Kopecky, Chantal; Genser, Bernd; März, Winfried (Clinical journal of the American Society of Nephrology, 2015)
Background and objectives Impairment of HDL function has been associated with cardiovascular events in patients with kidney failure. The protein composition of HDLs is altered in these patients, presumably compromising the cardioprotective effects of HDLs. This post hoc study assessed the relation of distinct HDL-bound proteins with cardiovascular outcomes in a dialysis population. Design, setting, participants, & measurements The concentrations of HDL-associated serum amyloid A (SAA) and surfactant protein B (SP-B) were measured in 1152 patients with type 2 diabetes mellitus on hemodialysis participating in The German Diabetes Dialysis Study who were randomly assigned to double-blind treatment of 20 mg atorvastatin daily or matching placebo. The association of SAA(HDL) and SP-B(HDL) with cardiovascular outcomes was assessed in multivariate regression models adjusted for known clinical risk factors. Results High concentrations of SAA(HDL) were significantly and positively associated with the risk of cardiac events (hazard ratio per 1 SD higher, 1.09; 95% confidence interval, 1.01 to 1.19). High concentrations of SP-B(HDL) were significantly associated with all-cause mortality (hazard ratio per 1 SD higher, 1.10; 95% confidence interval, 1.02 to 1.19). Adjustment for HDL cholesterol did not affect these associations. Conclusions In patients with diabetes on hemodialysis, SAA(HDL) and SP-B(HDL) were related to cardiac events and all-cause mortality, respectively, and they were independent of HDL cholesterol. These findings indicate that a remodeling of the HDL proteome was associated with a higher risk for cardiovascular events and mortality in patients with ESRD.